Development of Recombinant Antibody by Yeast Surface Display Technology - Mujahed I. Mustafa; Awad A. Alzebair; Ahmed Mohammed (Elsevier, 2024)
Recombinant antibodies have emerged as powerful tools in various fields, including therapeutics, diagnostics, and research applications. The selection of high-affinity antibodies with desired specificity is a crucial step in the development of recombinant antibody-based products. In recent years, yeast surface display technology has gained significant attention as a robust and versatile platform for antibody selection. This graphical review provides an overview of the yeast surface display technology and its applications in recombinant antibody selection. We discuss the key components involved in the construction of yeast surface display libraries, including the antibody gene libraries, yeast host strains, and display vectors. Furthermore, we highlight the strategies employed for affinity maturation and optimization of recombinant antibodies using yeast surface display. Finally, we discuss the advantages and limitations of this technology compared to other antibody selection methods. Overall, yeast surface display technology offers a powerful and efficient approach for the selection of recombinant antibodies, enabling the rapid generation of high-affinity antibodies for various applications.